Review of Current Trends in Web Usage Mining - Gayatri, Mantri; P.Satheesh, Dr.; R.Rajeshwara Rao, Dr. (International Journal of Engineering and Technology, 2018)
Due to incessantly growing of amount of data that is published over web pages, the world wide web (WWW) has impacted every facet of our lives. Due to the increase in size and also the complexity of web, it is necessary to search and retrieve information in an effective and efficient manner. The data in the web pages are semi-structured and heterogeneous making it difficult to access and a challenging issue. In web usage mining, knowledge is discovered effectively from usage patterns to serve the needs of various users. This paper offers a brief study and study of numerous techniques used for web usage mining Â Â